Increased Sales of Tofu Dregs Crackers Through Marketing Strategy Assistance and Promotional Innovations - Dien Rosa; Lilik Slamet Raharsono; Hery Prasetyo (Universitas Nahdlatul Ulama Lampung, 2021)
The city of Situbondo is currently the choice of entrepreneurs in the culinary business. For example, in the corner of the city along the main road entering Situbondo, there is a culinary business building, starting with street vendors, cafes, restaurants, shop houses, and a typical Situbondo souvenir center. One of the home industries in Panji Lor Village is Kristy's home industry. This home industry develops a superior product of tofu dregs crackers which is an innovation of KKN UNEJ 253 students and Mrs. Ine as the owner of the home industry. Through the 2018 partnership service program, this home industry received equipment assistance to cool cracker dough in the form of freezers and spinner equipment. Unfortunately, marketing promotion still relies on conventional methods so that the tofu dregs cracker is not well known to the public. Product packaging still relies on simple equipment so that packaging design is less desirable. In addition, the limitations of packaging equipment make tofu dregs crackers not durable and prone to damage. The proposed Partnership Service Program has a specific target of enabling service partners to implement tofu cracker marketing through offline and online media. Besides that, it also helps in the form of packaging equipment so that the tofu pulp crackers can last for a long time and minimize damage. The community service team has introduced online marketing through websites and other internet media and provided marketing strategy assistance. Keywords:economic creative sector, home industry, managament